Acute effects on maximal isometric force with and without knee wrap during squat exercise - Gomes, W. A.; Serpa, E. P.; Soares, E. G.; da Silva, J. J.; Corrêa, D.; de Oliveira, F. H. D.; de Abreu Neto, F.; Martins, G.; de Barros Vilela Junior, G.; Marchetti, P. H. (International Journal of Sports Science, 2014)
The aim of this study was to investigate the acute effects on maximal isometric force without and with two kinds of knee wraps (hard and soft) during squat exercise. Ten physical active participants were evaluated during this study. All subjects were familiarized with the isometric squat position in all conditions: without and with knee wrap (hard and soft stiffness). The squat exercise position was set up individually, guaranteeing their thigh parallel to the floor, the arms crossed on the chest, and the feet were kept always in the same position for all trials and conditions. All subjects performed three maximal isometric squat contractions in 3 different conditions: without knee wrap (WKW), with soft knee wrap (SKW) and with hard knee wrap (HKW). The peak of force was acquired at a 100Hz sampling frequency, during 3 seconds, 5 minutes of resting and all conditions were randomized. The results shows significant differences for peak force between conditions WKW and HKW (P=0.029, ES=1.27, d%=22%]) and WKW and SKW (P=0.038, ES=1.20, d%=21%]). The use of the knee wrap under the presented conditions seem to increase the maximal isometric force during the squat exercise, independent of the level of stiffness of the knee wrap.